Acid-sensing ion channels (ASICs) influence excitability of stellate neurons in the mouse cochlear nucleus - Cakir, Ziya; Yildirim, Caner; Buran, Ilay; Onalan, Ebru Etem; Bal, Ramazan (Springer Heidelberg, 2019)
Acid-sensing ion channels (ASICs) are voltage-independent and proton-gated channels. In this study, we aimed to test the hypothesis whether ASICs might be involved in modifying the excitability of stellate cells in the cochlear nucleus (CN). We determined gene expressions of ASIC1, ASIC2 and ASIC3 in the CN of BALB/mice. ASIC currents in stellate cells were characterized by using whole-cell patch-clamp technique. In the voltage-clamp experiments, inward currents were recorded upon application of 2-[N-Morpholino ethanesulfonic acid]-normal artificial cerebrospinal fluid (MES-aCSF), whose pH 50 was 5.84. Amiloride inhibited the acid-induced currents in a dose-dependent manner. Inhibition of the ASIC currents by extracellular Ca2+ and Pb2+ (10 mu M) was significant evidence for the existence of homomeric ASIC1a subunits. ASIC currents were increased by 20% upon extracellular application of Zn2+ (300 mu M) (p < 0.05, n = 13). In current-clamp experiments, application of MES-aCSF resulted in the depolarization of stellate cells. The results show that the ASIC currents in stellate cells of the cochlear nucleus are carried largely by the ASIC1a and ASIC2a channels. ASIC channels affect the excitability of the stellate cells and therefore they appear to have a role in the processing of auditory information.
Keywords: Acid-sensing ion channels; ASIC; Patch-clamp technique; Cochlear nucleus; Auditory pathway